2020
DOI: 10.1016/j.neuron.2020.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Gene Expression in the Aging Human Brain Reveal TDP-43 Proteinopathy Pathophysiology

Abstract: Highlights d A genome-wide screen identifies regulators of aging brain gene co-expression modules d TMEM106B and GRN variants show coordinated effects on the aging brain transcriptome d TMEM106B-regulated myelination and lysosomal genes connect amyloid-b and TDP-43 d An RBFOX1 variant upregulates innate immunity genes in the aging human brain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 74 publications
0
34
0
Order By: Relevance
“…Subsequently, genetic linkages were identified with a much broader spectrum of other neurodegenerative disorders including limbic-predominant age-related TDP-43 encephalopathy, Parkinson's disease and late-onset Alzheimer's disease (22,23,38). Moreover, genetic links were also confirmed with dissociation of cognitive performance in elderlies and differential aging in humans (16,30,45,47) as well as with increased neuronal proportion in Alzheimer's disease (16). Recently, a mutation in TMEM106B was identified as the underlying cause for a hypomyelinating leukodystrophy (35,46,51).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Subsequently, genetic linkages were identified with a much broader spectrum of other neurodegenerative disorders including limbic-predominant age-related TDP-43 encephalopathy, Parkinson's disease and late-onset Alzheimer's disease (22,23,38). Moreover, genetic links were also confirmed with dissociation of cognitive performance in elderlies and differential aging in humans (16,30,45,47) as well as with increased neuronal proportion in Alzheimer's disease (16). Recently, a mutation in TMEM106B was identified as the underlying cause for a hypomyelinating leukodystrophy (35,46,51).…”
Section: Discussionmentioning
confidence: 98%
“…Variations in TMEM106B were shown to affect the course of disease in both GRN-and C9orf72 carriers (7,8,28,40,42 (3,12,13,(22)(23)(24)31,38,48). Furthermore, TMEM106B was shown to play a role in the dissociation of cognition and neuropathology in elderly people (45) and TMEM106B was identified as a key genetic determinant of differential aging in the cerebral cortex (30,47). Finally, a dominant mutation in TMEM106B leads to a familial hypomyelinating leukodystrophy (35,46).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, a recent study identified GRN and TMEM106B as two of the five risk factors for a recently recognized disease entity, limbic‐predominant age‐related TDP‐43 encephalopathy (LATE) (Nelson et al , ). These two genes were also found to be associated with TDP‐43 proteinopathy and coordinate with each other to regulate gene expression in a genome‐wide transcription study (Yang et al , ). Furthermore, GRN and/or TMEM106B polymorphisms are associated with FTLD caused by C9ORF72 mutations (van Blitterswijk et al , ; Deming & Cruchaga, ; Gallagher et al , ; Lattante et al , ), cognitive impairment in amyotrophic lateral sclerosis (ALS) (Vass et al , ) and Parkinson's disease (PD) (Baizabal‐Carvallo & Jankovic, ; Tropea et al , ), and pathological presentation of Alzheimer's disease (AD) (Lee et al , ; Rutherford et al , ; Kamalainen et al , ; Perry et al , ; Sheng et al , ; Xu et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In another example, the effects of two genetic variants, APOEε4 and a haplotype in TMEM106B, were shown to converge on altered expression of a group of co-expressed genes called module 110: they independently alter the expression of module 110, which then contributes to the accumulation of TDP-43 proteinopathy. This model was developed in a data-driven manner using rigorous statistics, and, while the model needs to be validated, it is consistent with known biology of TDP-43 pathology, suggesting that large datasets can begin to define complex relationships (43).…”
Section: Transcriptome In Admentioning
confidence: 99%